Replication of ribosomal DNA in Arabidopsis occurs both inside and outside the nucleolus during S phase progression - Dvořáčková, Martina; Raposo, Berta; Matula, Petr; Fuchs, Joerg; Schubert, Veit; Peška, Vratislav; Desvoyes, Bénédicte; Gutierrez, Crisanto; Fajkus, Jiří (Journal of cell science, 2018)
Ribosomal RNA genes (rDNA) have been used as valuable experimental systems in numerous studies. Here, we focus on elucidating the spatiotemporal organisation of rDNA replication in Arabidopsis thaliana To determine the subnuclear distribution of rDNA and the progression of its replication during the S phase, we apply 5-ethynyl-2'-deoxyuridine (EdU) labelling, fluorescence-activated cell sorting, fluorescence in situ hybridization and structured illumination microscopy. We show that rDNA is replicated inside and outside the nucleolus, where active transcription occurs at the same time. Nascent rDNA shows a maximum of nucleolar associations during early S phase. In addition to EdU patterns typical for early or late S phase, we describe two intermediate EdU profiles characteristic for mid S phase. Moreover, the use of lines containing mutations in the chromatin assembly factor-1 gene fas1 and wild-type progeny of fas1xfas2 crosses depleted of inactive copies allows for selective observation of the replication pattern of active rDNA. High-resolution data are presented, revealing the culmination of replication in the mid S phase in the nucleolus and its vicinity. Taken together, our results provide a detailed snapshot of replication of active and inactive rDNA during S phase progression.
Keywords: Flow cytometry; ribozomální DNA; DNA, Ribosomal; Nucleolus; Cell Nucleolus; Transcription, Genetic; S Phase; replikace DNA; Deoxyuridine; A. thaliana rDNA; genetická transkripce; Plant Roots; Structured illumination microscopy; Arabidopsis; deoxyuridin; S fáze; DNA Replication; kořeny rostlin; buněčné jadérko; Replication